Oral Mucositis in Pediatric Acute Lymphoblastic Leukemia Patients: Evaluation of Microbiological and Hematological Factors. (1st August 2015) - Mendonça, Regina Maria Holanda de; Araújo, Marcela de; Levy, Carlos Emilio; Morari, Joseane; Silva, Rosângela A.; Yunes, José Andres; Brandalise, Silvia Regina
Abstract : Objective : to investigate the associations of oral microbiota, leucocytes count, neutrophil count, platelet counts and hemoglobin level, and the severity of oral mucositis in pediatric patients with acute lymphoblastic leukemia (ALL) receiving chemotherapy. Materials and Methods : 71 prospective patients were included. Analyses of oral microbiota and blood sample were conducted on days 14 (D14) and 56 (D56) of the Brazilian GBTLI-99 treatment protocol. Herpes simplex virus ( HSV ) identification was performed by PCR followed by DNA sequencing analysis. Bacteria and fungi identification was obtained by standard microbiological culture tests. Results : 103 episodes of mucositis occurred, being 65 at D14 and 38 at D56. Most cases positive for herpes viral DNA sequences were identified as HSV-1 . At D14, we found a significant association between the severity of mucositis and presence of HSV-1 ( p = 0.0347), Candida spp. ( p = 0.0078), and low platelet count ( p = 0.0064). At D56, we found a significant association between the severity of mucositis and the presence of HSV-1 ( p = 0.0317), previous HSV-1 presence on D14 ( p < 0.0001) and neutrophil count ( p = 0.0211). Clinical relevance : the identification of risk factors for mucositis in children and adolescents may contribute to the development of new strategies for prevention and/or treatment, reducing the complications associated with this condition. Conclusions : the presence of HSV, platelet count, and Candida spp. presence at D14 of ALL induction treatment is associated with increased severity of mucositis in children and adolescents. At D56 of ALL treatment, mucositis severity was associated with neutrophil count, HSV presence, and previous presence of HSV (at D14).